Saffron Flower Extract Promotes Scratch Wound Closure of Keratinocytes and Enhances VEGF Production - Verjee, Sheela; Garo, Eliane; Pelaez, Sarah; Fertig, Orlando; Hamburger, Matthias; Butterweck, Veronika (Planta Medica, 2017)
During saffron (Crocus sativus) spice production, large amounts of floral biowaste are generated. It was the aim of this study to develop a value-added product from saffron floral biowaste to be used as a natural cosmetic ingredient. HPLC-PDA-MS analysis of saffron flower extracts revealed the presence of flavonols with the highest amounts in the acetone extract. Kaempferol-3-O-sophoroside was identified as the main flavonoid in the acetone extract (saffron flower acetone extract). Saffron flower acetone extract and kaempferol-3-O-sophoroside were tested in HaCaT cells for potential effects on cell migration, proliferation, and for anti-inflammatory properties. Saffron flower acetone extract concentration dependently (50–200 µg/mL) augmented cell proliferation, as indicated by an increased BrdU-incorporation, while kaempferol-3-O-sophoroside (1–50 µM) had no effect. Furthermore, treatment of HaCaT cells with saffron flower acetone extract, but not with kaempferol-3-O-sophoroside, concentration-dependently increased vascular endothelial growth factor secretion (control 49.72 pg/mL vs. saffron flower acetone extract at 200 µg/mL 218.60 pg/mL). Cell migration was determined using time-lapse microscopy and a modification of the scratch-wound assay in which saffron flower acetone extract significantly improved wound closure compared to the untreated control. Overproduction of the proinflammatory cytokines interleukin-8 and interleukin-6 in HaCaT cells was induced by TNF-α. Kaempferol-3-O-sophoroside (10–50 µM), but not saffron flower acetone extract, inhibited TNF-α-induced IL-8 secretion. The effect was comparable to 10 µM hydrocortisone (positive control). Interestingly, saffron flower acetone extract further increased IL-6 levels in TNF-α-treated HaCaT cells in a concentration-dependent manner. In summary, the pronounced wound healing properties of saffron flower acetone extract present a promising application for the cosmetic industry.
Keywords: Crocus sativus; Iridaceae; biowaste; cell proliferation; cell migration; inflammation; kaempferol-3-O-sophoroside; cosmetics